KRITIK TERHADAP HONOR KILLING DI PAKISTAN: PERSPEKTIF MAQASHID SYARIAH - CONTESA, YENIS; Surwandono (The Indonesian Islamic Studies and International Relations Association (Insiera), 2024)
Islam is a religion that respects and upholds human values. Honor killing is a phenomenon that occurs in many countries, one of which is Pakistan. Therefore, this paper examines the practice of honour killing from the perspective of maqashid sharia. This paper uses a qualitative method with a literature study approach consisting of books, news, and journals relevant to this research. The findings in this study found that first, Pakistani society uses the tradition of honor killing as a legal tool for those who violate family honour. Second, the development of the practice of honor killing in Pakistan is due to cultural traditions and adapting from the laws of Qisas and Diyat. In the perspective of maqashid sharia, the practice of honor killing is contrary to the principle of al-Dharuriyat al-Khamsah, namely religion and soul. Through the principles in maqashid sharia, everything that contradicts the Qur'an and Sunnah is considered as behaviour that is not in accordance with Islamic sharia.